Pacemaker and Defibrillator Implantation and Programming in Patients with Deep Brain Stimulation. Issue 2 (May 2019) - Elliott, Mark; Momin, Sheikh; Fiddes, Barnaby; Farooqi, Fahad; Sohaib, SM Afzal
No abstract available